If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 = -3x + -47 Reorder the terms: -10 = -47 + -3x Solving -10 = -47 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -10 + 3x = -47 + -3x + 3x Combine like terms: -3x + 3x = 0 -10 + 3x = -47 + 0 -10 + 3x = -47 Add '10' to each side of the equation. -10 + 10 + 3x = -47 + 10 Combine like terms: -10 + 10 = 0 0 + 3x = -47 + 10 3x = -47 + 10 Combine like terms: -47 + 10 = -37 3x = -37 Divide each side by '3'. x = -12.33333333 Simplifying x = -12.33333333
| 5x^2-4x+2whenx=-2 | | 2ax^2-2a^2x+10x-10a=0forx | | x^4+2x^2-x+4=0 | | 48x+y=340 | | 2ax^2-2a^2x+10x-10a=0 | | 5r^4-3125= | | y^4+4y^2+5y=0 | | 2(3x+5)=32 | | x^4+4y^2+5y=0 | | 2.5f=40 | | 6-7(x-1)x=7 | | 20+x=3x | | -89=5x+4x+10 | | 10/10= | | 5+3x=10-2x | | x/3-x/4-1/6=7/3? | | 5t^2-7t-6=0 | | 2d+3whend=8 | | -6y^2-4y-2=0 | | 7y^2-50y+75=0 | | -3b+7=-15+26 | | f(x)=-2+8x-7 | | 8+(9t+9)= | | 5-4(x+3)=2x+5(3x-8)-3(1-6x) | | 2+2x=x+5 | | -kx=p-4x | | x-(-8)=-7 | | 15(16x-40)=55 | | 6(x-4)-8=4 | | [x-5]=15 | | x+7(3)-6=x | | 2/3(9b-2f)=36 |